Fenomena Isomorfik (Koebner) and Isotopik (Wolf’s) dari Psoriasis Pasca-Herpes-Zoster: Sebuah Kompilasi Studi Kasus dan Tinjauan Naratif. - Lidya Oktaviani Siauw; Yuliana Teguh (Cermin Dunia Kedokteran, 2024)
Koebner phenomenon is defined as the development of psoriatic lesions on previously healthy skin of a psoriasis patient following skin trauma. A related skin reaction, known as Wolf's isotopic response, involves the appearance of a new skin condition in an area of healed dermatosis; in many cases, from herpes zoster. The exact cause of this link is not fully understood, but it may involve neuroimmune system and its neuromediators, particularly substance P. This paper serves as a reminder on the importance of recognizing dermatologic phenomena.